DNP NMR spectroscopy enabled direct characterization of polystyrene-supported catalyst species for synthesis of glycidyl esters by transesterification. Issue 16 (23rd March 2022) - Tanaka, Shinji; Nakajima, Yumiko; Ogawa, Atsuko; Kuragano, Takashi; Kon, Yoshihiro; Tamura, Masanori; Sato, Kazuhiko; Copéret, Christophe
Abstract : We demonstrated that DNP-enhanced NMR spectroscopy enables the direct and detailed characterization of polymer-supported alkylammonium catalysts. Abstract : Polymer-supported catalysts have been of great interest in organic syntheses, but have suffered from the difficulty in obtaining direct structural information regarding the catalyst species embedded in the polymer due to the limitations of most analytical methods. Here, we show that dynamic nuclear polarization (DNP)-enhanced solid-state NMR is ideally positioned to characterize the ubiquitous cross-linked polystyrene (PS)-supported catalysts, thus enabling molecular-level understanding and rational development. Ammonium-based catalysts, which show excellent catalytic activity and reusability for the transesterification of methyl esters with glycidol, giving glycidyl esters in high yields, were successfully characterized by DNP 15 N NMR spectroscopy at 15 N natural abundance. DNP 15 N NMR shows in particular that the decomposition of quaternary alkylammonium moieties to tertiary amines was completely suppressed during the catalytic reaction. Furthermore, the dilute ring-opened product derived from glycidol and NO3 − was directly characterized by DNP 15 N CPMAS and 1 H– 15 N and 1 H– 13 C HETCOR NMR using a 15 N enriched (NO3 ) sample, supporting the view that the transesterification mechanism involves an alkoxide anion derived from an epoxide and NO3 − . In addition, the detailed analysis of a used catalyst indicated that the adsorption of products on the cationic center is the major deactivation step in this catalysis.